Politisasi Isu Agama di Media Massa: Strategi Politik Hos Cokroaminoto dalam Surat Kabar Djawi Hisworo (1918): The Politicization of Religious Issues in the Mass Media: Hos Cokroaminoto's Political Strategy in the Djawi Hisworo Newspaper (1918) - Fajar, Ahmad (Nur Science Institute, 2021)
HOS Cocroaminoto is a politician as well as the leader of Sarekat Islam movement at the beginning of the 20th century. He was an active figure in the early world of the movement in the Hindia Belanda. In its political activity in 1918, he politicized the polemic of blasphemy in the newspapers of Djawi Hisworo to strengthen his political standing and attack his enemies. Through this politicization, Cokrominoto managed to attract many followers and mobilize the masses consisting of muslim. In this study, the author uses historical research methods wich include soirce criticism, interpretation, and historical writing.This writing is written with analitycal descriptive type. Research resource, among others: (1) Cokroaminoto politicized by attracting modernist Muslims to revive the branches of Sarekat Islam wich at the time were neglecte. (2) He also succeeded in estabilishing the Tentara Kandjeng Nabi Muhammad for the media movement. (3) He also managed to raise funds from Muslim merchants so many. Cokroaminoto then expelled enemies in the Communist-leaning Sarekat Islam which at the time became an obstacle for him to carry out his political activities.